Dendritic Fibrous Nanosilica for Catalysis, Energy Harvesting, Carbon Dioxide Mitigation, Drug Delivery, and Sensing. Issue 20 (9th October 2017) - Maity, Ayan; Polshettiwar, Vivek
Abstract: Morphology‐controlled nanomaterials such as silica play a crucial role in the development of technologies for addressing challenges in the fields of energy, environment, and health. After the discovery of Stöber silica, followed by that of mesoporous silica materials, such as MCM‐41 and SBA‐15, a significant surge in the design and synthesis of nanosilica with various sizes, shapes, morphologies, and textural properties has been observed in recent years. One notable invention is dendritic fibrous nanosilica, also known as KCC‐1. This material possesses a unique fibrous morphology, unlike the tubular porous structure of various conventional silica materials. It has a high surface area with improved accessibility to the internal surface, tunable pore size and pore volume, controllable particle size, and, importantly, improved stability. Since its discovery, a large number of studies have been reported concerning its use in applications such as catalysis, solar‐energy harvesting, energy storage, self‐cleaning antireflective coatings, surface plasmon resonance‐based ultrasensitive sensors, CO2 capture, and biomedical applications. These reports indicate that dendritic fibrous nanosilica has excellent potential as an alternative to popular silica materials such as MCM‐41, SBA‐15, Stöber silica, and mesoporous silica nanoparticles. This Review provides a critical survey of the dendritic fibrous nanosilica family of materials, and the discussion includes the synthesis and formation mechanism, applications in catalysis and photocatalysis, applications in energy harvesting and storage, applications in magnetic and composite materials, applications in CO2 mitigation, biomedical applications, and analytical applications. Abstract : All‐in‐one nanomaterial : This Review provides a critical survey of the dendritic fibrous nanosilica (DFNS) family of materials, and the discussion includes synthesis, mechanism of formation, and applications in catalysis, photocatalysis, energy harvesting and storage, magnetic and composite materials, CO2 mitigation, biomedical applications, and analytical applications.